Hepatokines and metabolism: Deciphering communication from the liver - Sharon O. Jensen-Cody; Matthew J. Potthoff (Elsevier, 2021)
Background: The liver is a key regulator of systemic energy homeostasis and can sense and respond to nutrient excess and deficiency through crosstalk with multiple tissues. Regulation of systemic energy homeostasis by the liver is mediated in part through regulation of glucose and lipid metabolism. Dysregulation of either process may result in metabolic dysfunction and contribute to the development of insulin resistance or fatty liver disease. Scope of review: The liver has recently been recognized as an endocrine organ that secretes hepatokines, which are liver-derived factors that can signal to and communicate with distant tissues. Dysregulation of liver-centered inter-organ pathways may contribute to improper regulation of energy homeostasis and ultimately metabolic dysfunction. Deciphering the mechanisms that regulate hepatokine expression and communication with distant tissues is essential for understanding inter-organ communication and for the development of therapeutic strategies to treat metabolic dysfunction. Major conclusions: In this review, we discuss liver-centric regulation of energy homeostasis through hepatokine secretion. We highlight key hepatokines and their roles in metabolic control, examine the molecular mechanisms of each hepatokine, and discuss their potential as therapeutic targets for metabolic disease. We also discuss important areas of future studies that may contribute to understanding hepatokine signaling under healthy and pathophysiological conditions.